1697 Undergraduate Otolaryngology: Enhancing Interest and Education with Hands-on Simulation. (12th October 2021) - Hirniak, J; Jain, A; Van, M; Kokotkin, I; Vaghela, M; Churchill, T; Zargaran, A
Abstract: Introduction: With cancelled student placements due to the COVID-19 pandemic, there is a shift towards non-patient-facing methods to deliver medical education. The aim was to design, deliver and evaluate an ENT course for undergraduate medical students. Method: A three-part simulation course on common and emergency ENT conditions was delivered by ENT trainees to undergraduate medical students (n = 50). It involved theoretical and hands-on experience with otoscopy on head models; nasoendoscopy and epistaxis management with upper airway head models and nasal packing kits; and management of compromised airways using critical airway models, airway adjuncts, intubation and cricothyroidotomy kits. Delegates were given pre- and post-course questionnaires, with another at six-weeks to test knowledge retention. Results were statistically analysed using paired and independent sample t-tests. Results: A statistically significant improvement in post-test knowledge of 55% ( p <0.01) was observed. Delegates also demonstrated a sustained improvement of 51% ( p <0.01) six-weeks later compared to baseline knowledge. 76% and 80% reported improved confidence managing epistaxis and performing intubation respectively; 46% reported increased interest in pursuing ENT as a potential career. Conclusions: This study demonstrated statistically significant and sustained improvements in knowledge about common and emergency ENT concepts. ENT simulation therefore represents an efficacious mechanism for teaching key ENT concepts and improving confidence in undergraduate medical students, whilst improving interest in pursuing ENT as a career. Additionally, simulation is an invaluable educational adjunct that may foster more realistic, impactful, and safer educational experiences for medical students whilst exposure to patients is minimised due to the current pandemic.